The role of beliefs, conceptualisations and experiences of OBE in teaching practice - Ramukumba, Mokholelana Margaret (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Curriculum Studies))--University of Stellenbosch, 2010.